Lesser Pumpkin Fly, Ethiopian Fruit Fly, Cucurbit Fly, Dacus ciliatus (Loew) (Insecta: Diptera: Tephritidae) - Howard V. Weems (EDIS)
The lesser pumpkin fly is one of several fruit flies found in Africa and Asia, which could become serious pests of Florida agricultural crops if introduced into this state. This revised 2-page fact sheet was written by H. V. Weems, Jr., and published by the UF Department of Entomology and Nematology, March 2012.